Population structure and core collection construction of apricot (Prunus armeniaca L.) in North Africa based on microsatellite markers. Issue 1 (31st July 2015) - Bourguiba, Hedia; Batnini, Mohamed-Amine; Krichen, Lamia; Trifi-Farah, Neila; Audergon, Jean-Marc
Abstract : North Africa enclosed original apricot genetic resources with the cohabitation of grafting and seed-propagated accessions. In this study, we assessed the genetic diversity and population structure of 183 apricot accessions using 24 microsatellite markers distributed evenly in the Prunus genome. A total of 192 alleles and a high level of gene diversity (0.593) were detected among the whole panel. Genetic structure analysis revealed the presence of four genetic clusters. We also found that both geographical origin and mode of propagation are important factors structuring genetic diversity in apricot species. Results confirmed the presence of gene exchange between the northern and southern countries of the Mediterranean Basin. Subsequently, a core collection of 98 accessions based on M (maximization) strategy showing 99.47% of allele retention ratio was constructed. No significant differences for Shannon's information index and Nei's diversity index were observed between the core and entire collections. Our results provide an effective aid for future germplasm preservation and conservation strategies as well as genetic association studies development in relation to phenotypic data.